Impact of Lymph Node Burden on Survival of High-risk Prostate Cancer Patients Following Radical Prostatectomy and Pelvic Lymph Node Dissection - Moris, Lisa; Van den Broeck, Thomas; Tosco, Lorenzo; Van Baelen, Anthony; Gontero, Paolo; Karnes, Robert Jeffrey; Everaerts, Wouter; Albersen, Maarten; Bastian, Patrick J.; Chlosta, Piotr; Claessens, Frank; Chun, Felix K.; et al. (Frontiers in Surgery, 2016)
Aim: To determine the impact of the extent of lymph node invasion (LNI), on long-term oncological outcomes after radical prostatectomy (RP). Material and methods: In this retrospective study we examined the data of 1249 high-risk, non-metastatic PCa patients treated with RP and pelvic lymph node dissection (PLND) between 1989 and 2011 at 8 different tertiary institutions. We fitted univariate and multivariate cox models to assess independent predictors of cancer specific survival (CSS) and overall survival (OS). The number of positive LN was dichotomized according to the most informative cut-off predicting CSS. Kaplan-Meier curves assessed CSS and OS rates. Only patients with at least 10 LNs removed at PLND were included. This cut-off was chosen as a surrogate for a well performed PNLD. Results: Mean age was 65 years (median: 66, IQR 60-70). Positive surgical margins were present in 53.7% (n=671). Final Gleason score was 2-6 in 12.7% (n=158), 7 in 52% (n=649) and 8-10 in 35.4% (n=442). The median number of LNs removed during PLND was 15 (IQR 12-17). Of all patients, 1128 (90.3%) had 0-3 positive LNs, while 126 (9.7%) had ≥4 positive LNs. Patients with 0-3 positive LNs had significantly better CSS outcome at 10-year follow-up compared to patients with ≥4 positive LNs (87% vs. 50%; p < 0.0001). Similar results were obtained for OS, with a 72% vs. 37% (p <0.0001) survival at 10 years for patients with 0-3 vs. ≥4 positive LNs, respectively. At multivariate analysis, final Gleason score 8-10, salvage ADT therapy and ≥4 (vs <4) positive LNs were predictors of worse CSS and OS. Pathological stage pT4 was an additional predictor of worse CSS. Conclusions: Four or more positive LNs, pathological stage pT4 and final Gleason score 8-10 represent independent predictors for worse CSS in patients with high-risk PCa. Primary tumor biology remains a strong driver of tumor progression and patients having ≥4 positive LNs could be considered an enriched patient group in which novel treatment strategies should be studied.